Relevansi Teori Behaviorisme Menurut Edward Lee Thorndike Dan J.B Watson Terhadap Pendidikan Agama Islam - Azizah, Miftakhul Nuuril (Educatia : Jurnal Pendidikan dan Agama Islam, 2023)
Learning theory is a coherent set of general principles and explanations of a number of computations and innovations associated with using learning events. Behaviorism learning theory can be used to help the learning process. However, it is known that many experiments in behaviorism theory are carried out using animals, which raises the question whether behaviorism learning theory is in line with Islamic teachings and can be used in Islamic education. This research is a library research which is analyzed by using content analysis technique. The results of this study are found to be relevant between behaviorism learning theory and Islamic education, as follows: (1) Behaviorism learning theory can be used to help the learning process of Islamic education (2) Behaviorism learning theory is a learning theory that is in line with Islamic teachings. (3) The existence of classical conditioning, repetition and reinforcement in behaviorsime theory which is also used in Islamic education learning (4) Behaviorism learning theory according to Edward Lee Thorndike contains four laws, namely: law of radiness (law of readiness), law of exercise (law of practice), law of effect (law of practice), and law of attitude (law of attitude), which are in line/related to the learning process of Islamic education.